FORMATION OF INFORMATION COMPETENCE OF STUDENTS USING MODERN ELECTRONIC MEANS - Fayzieva , Shohista Yusupovna (Innovative Development in Educational Activities, 2023)
This article provides a definition of information competence, the importance of modern computer programs in the development of information competence of students, components and criteria of information competence, indicators for measuring and determining the level of information competence. Also in the article, the computer network model creator Arena-Rockwell, ExtendSim-Imagine Than Inc, Anylogic-XJ Technologies, NetMaker XA, Opnet-OPNET Technologies, Cisco Packet Tracer modern programs about briefly stopping the past.